Real health care in the face of the vulnerability of the nursing student - Sosa-García, Betsy Corina; García-Reza, Cleotilde; Arias-Rojas, Mauricio (Universidad y Salud, 2021)
Introduction: The exchange of daily practicing experiences with peers is useful for students to learn about nursing care. Objective: To understand the social representations of health care that are constructed from the daily life experiences of the Mexican nursing student. Materials and methods: A qualitative study based on the social representation theory with 46 students who carried out clinical practices. A semi-structured interview was applied, which was analyzed through grouping of empirical categories that support the composition of the subsequent results, comparing the data with reports from the participants. Results: The conception of the health care process is structured with ranges that represent the social aspects of the students during their training, which in turn makes them vulnerable. The experiences are constructed and re-constructed as a consequence of the students’ eagerness to discover their experiences in health care in order to respond to their challenges. However, these experiences affect the students’ world, disrupting their peace of mind. Conclusions: Interaction processes position students in the face of the social world of health care based on philosophical bases in order to reflect with their being and doing, an action that guides their behavior in the daily care of the other.